MENGEFEKTIFKAN FUNGSI MANAJEMEN DALAM PERBAIKAN MUTU PENDIDIKAN - Karimullah, Karimullah (STAIN Pamekasan, 2010)
Abstract: Education has a very important role in the process of improving the quality of human resources. Improving the quality of education is an integrated process with the process of improving the quality of human resources. One effort to develop the quality of education is by optimizing the function of education management involving planning (planning), organization (organizing), leadership (leading) and monitoring (controlling). For running good management and achieving optimal results, it needs a strong principal, having a clear vision and mission and being able to translate both in policy formulations and measurable goals for creating a climate and working atmosphere to empower employees to do their best.